Discounting and climate policy - Van der Ploeg, R (University of Oxford, 2020)
The social rate of discount is a crucial driver of the social cost of carbon (SCC), i.e. the expected present discounted value of marginal damages resulting from emitting one ton of carbon today. Policy makers should set carbon prices to the SCC using a carbon tax or a competitive permits market. The social discount rate is lower and the SCC higher if policy makers are more patient and if future generations are less affluent and policy makers care about intergenerational inequality. Uncertainty about the future rate of growth of the economy and emissions and the risk of macroeconomic disasters (tail risks) also depress the social discount rate and boost the SCC provided intergenerational inequality aversion is high. Various reasons (e.g. autocorrelation in the economic growth rate or the idea that a decreasing certainty-equivalent discount rate results from a discount rate with a distribution that is constant over time) are discussed for why the social discount rate is likely to decline over time. A declining social discount rate also emerges if account is taken from the relative price effects resulting from different growth rates for ecosystem services and of labour in efficiency units. The market- based asset pricing approach to carbon pricing is contrasted with a more ethical approach to policy making. Some suggestions for further research are offered.